PENGASUHAN ANAK PASCAPERCERAIAN (Studi Pustaka dengan Perspektif Pendidikan Informal Islam) - Ali Rohmad (LP2M IAIN Tulungagung, 2016)
Everyone who establish relationships marriage course, wanted a harmonious relationship with her partner, developing relationships with partner until his death. But in reality not every marriage lasted harmonious as expected, some even marriage to end in divorce. After divorce problems that often occur is about parenting, not just neighbor custody of children, but also the psychology of children, especially those still at the early age phase. This article seeks to discuss how the characteristics of the child’s development in a phase after divorce early age 0-6 years which need to be addressed during the actualization of care. In addition to the articles also will be reviewed how parenting after divorce activity in a phase early ages 0-6 years with an Islamic perspective of informal education.Kata Kunci: Pengasuhan, Pascaperceraian, Pendidikan Informal Islam